East German Intellectuals and the Unification of Germany : An Ethnographic View - Bednarz, Dan (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book discusses the reunification of Germany and the negative impacts that this had on East German intellectuals. The book is an ethnographic account of how the intellectuals of East Germany reacted to the demise of their nation, their "dream" of a socialist world, and unification with capitalist West Germany. Part I covers unification, 1990-91; Part II presents a quarter century later follow-up with one-fourth of those interviewed in 1990-91; and Part III examines the case from three social science perspectives.
Keywords: Social sciences.; Russia -- History.; Europe, Eastern -- History.; Ethnography.; Historical sociology.; Political sociology.; elektronické knihy; electronic books